2003
DOI: 10.1074/jbc.m308843200
|View full text |Cite
|
Sign up to set email alerts
|

SeqA Protein Stimulates the Relaxing and Decatenating Activities of Topoisomerase IV

Abstract: The SeqA protein, which prevents overinitiation of chromosome replication, has been suggested to also participate in the segregation of chromosomes in Escherichia coli. Using a bacterial two-hybrid system, we found that SeqA interacts with the ParC subunit of topoisomerase IV (topo IV), a type II topoisomerase involved in decatenation of daughter chromosomes and relief of topological constraints generated by replication and transcription. We demonstrated that purified SeqA protein stimulates the activities of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 46 publications
1
43
0
1
Order By: Relevance
“…Results from bacterial two-hybrid assays indicated that the CTD of E. coli ParC can interact with SeqA protein, a DNA binding modulator of chromosome replication (51). As SeqA was found to preferentially bind hemimethylated DNA and thus localize primarily behind the replication fork, E. coli Topo IV was proposed to be recruited to this general area by SeqA to disentangle precatenanes caused by replication.…”
Section: Resultsmentioning
confidence: 99%
“…Results from bacterial two-hybrid assays indicated that the CTD of E. coli ParC can interact with SeqA protein, a DNA binding modulator of chromosome replication (51). As SeqA was found to preferentially bind hemimethylated DNA and thus localize primarily behind the replication fork, E. coli Topo IV was proposed to be recruited to this general area by SeqA to disentangle precatenanes caused by replication.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to MukB, numerous examples of proteins with physical and/or functional interactions with ParC have been reported, including the DNA polymerase III holoenzyme, FtsK, MreB, and SeqA (61)(62)(63)(64). Marians and co-workers have clearly shown functional significance for the interactions of Topo IV with the first of these three binding partners (61,62,64).…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that the association of NDP reductase within this hyperstructure could be a requirement not only for the synthesis of precursors for replication but also for the correct conformation of the hyperstructure required for the location of the replication fork and for chromosome segregation. In this sense it is interesting to mention the connection of topoisomerase IV (required for decatenation of sister chromosomes and segregation) with SeqA (a hemimethylated DNA-binding protein located at initiation and at the replication fork [21]), and with FtsK (a translocase required to facilitate chromosome dimer resolution, to clear DNA from the closing septum, and to form septa), and with DnaX (which codes for the γ and τ  subunits of DNA polymerase III holoenzyme [22]). Studies on B. subtilis support the idea that the replication factory, for most of the replication cycle with a fixed mid-cell location [23], is likely to be co-…”
Section: Discussionmentioning
confidence: 99%